Electroencephalogram dynamics in children during different levels of anaesthetic depth. Issue 10 (October 2017) - Koch, S.; Stegherr, A.M.; Mörgeli, R.; Kramer, S.; Toubekis, E.; Lichtner, G.; von Dincklage, F.; Spies, C.
Highlights: EEG dynamics in children are strongly influenced by anaesthetic depth and to a lesser extent by age. For children under deep anaesthesia, age dependency of EEG parameters is only seen for total power. In children under light anaesthesia relative beta band power increases linearly with age. Abstract: Objective: Anaesthesia-induced dynamics in EEG are dependent on age and level of anaesthesia, but distinct characterisation in children is incomplete. Here we analyse EEG dynamics in children related to age and level of anaesthesia. Methods: Frontal EEG recordings were obtained from 93 children (0–19 years) during routine clinical anaesthesia. EEG segments were selected at four different levels of anaesthesia: emergence, light anaesthesia, deep anaesthesia, and very deep anaesthesia. Results: Total power differed significantly over age at deep (R 2  = 0.314; p < 0.0001) and very deep anaesthesia (R 2  = 0.403; p < 0.0001). Relative beta band power at light anaesthesia increased linearly with age (R 2  = 0.239; p < 0.0001). Level of anaesthesia caused significant differences for relative delta band power (increasing with anaesthetic depth), for relative beta band power and for spectral edge frequency (decreasing with anaesthetic depth) for all children (p < 0.0001). Conclusions: EEG parameter in children were primary dependent on anaesthetic depth, where beta band power, delta band power and spectral edge frequency showed a linear relation. Age-dependency during anaesthesia procedure were only seen for single EEG parameters. Significance: Different levels of anaesthesia can be identified by relative beta band power, relative delta band power and spectral edge frequency irrespective of the children's age.